2019
DOI: 10.1002/hep4.1389
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of Hepatitis C Virus Is Associated With Reduction in Hematologic Malignancies: Major Differences Between Interferon and Direct‐Acting Antivirals

Abstract: It is unclear whether eradication of hepatitis C virus (HCV) leads to a reduction in the risk of hematologic malignancies. We aimed to determine the impact of sustained virologic response (SVR) induced by either direct‐acting antivirals (DAAs) or interferon (IFN) on the risk of hematologic malignancies. We identified 69,581 patients who initiated antiviral treatment in the Veterans Affairs national health care system from January 1, 1999, to December 31, 2015, including 40,410 (58%) IFN‐only regimens, 4,546 (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…Treatment response was not known in this study. Another study showed that IFN‐induced SVR was significantly associated with a reduction of the risk of lymphoma, multiple myeloma, MGUS and haematological malignancies combined, but these associations were not observed with DAA‐induced SVR during a mean follow‐up of 2.9 years 38 . Neither IFN‐induced SVR nor DAA‐induced SVR was associated with the risk of colon cancer or prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment response was not known in this study. Another study showed that IFN‐induced SVR was significantly associated with a reduction of the risk of lymphoma, multiple myeloma, MGUS and haematological malignancies combined, but these associations were not observed with DAA‐induced SVR during a mean follow‐up of 2.9 years 38 . Neither IFN‐induced SVR nor DAA‐induced SVR was associated with the risk of colon cancer or prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, El-Serag et al ( 1 ) also reported that successful DAA treatment resulting in SVR was not associated with reduction in NHL risk. Moreover, in a comparative study of the risk of hematologic malignancies following IFN-induced SVR and DAA-induced SVR, researchers showed that IFN-induced SVR significantly reduced the risk of hematologic malignancies, including lymphoma and myeloma (adjusted hazard ratio, 0.67; 95% confidence interval, 0.53-0.84), whereas DAA-induced SVR was not associated with a reduction in the risk of hematologic malignancies (adjusted hazard ratio, 1.08; 95% confidence interval, 0.66-1.78) ( 33 ). Thus, these results suggested that the development of malignant lymphomas may occur after HCV clearance with DAAs, supporting recent case reports ( 22-26 ), including the present case ( Table I ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, genetic mutations derived from either acute or chronic HCV infection are known to persist, even after HCV clearance ( 31 ). Notably, unlike conventional IFN therapy, DAAs lack the ability to either directly treat a subclinical malignancy or enhance an immune response to malignancy ( 33 ). In particular, in terms of immune response, HCV clearance with DAAs was reported to be associated with the persistence of CD4 regulatory T cells ( 34 ), which inhibit cytotoxic CD8 + T cells exposed to B-cell NHLs ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little evidence available examining the impact of anti‐HCV treatment on risk of non‐hepatic cancer. To date, three studies evaluated the association between HCV treatment and rate of haematologic malignancies among HCV‐infected veterans 19,22,38 . Evidence indicated that patients who achieved a sustained virologic response with interferon‐based anti‐viral therapy had a significantly decreased risk of lymphoma of 30%‐36%.…”
Section: Discussionmentioning
confidence: 99%